Designing a neighborhood to prevent crime and increase physical activity: a case study among African-American women in Kansas City, Missouri - Jones, Cydnie (Kansas State University, 2015)
Obesity levels—related to an increase of physical inactivity—are rapidly rising in the United States (CDC 2010; Office of Disease Prevention and Health Promotion 2008). Reportedly, African-American women have the highest obesity rates when compared to any other demographic in the United States—especially those residing in crime-plagued urban environments (CDC 2010). Yet active living strategies by designers have been least effective amongst this demographic (Day 2006). Researchers report crime-safety perceptions are one of the biggest environmental factors influencing physical activity levels amongst low-income African-American women (Foster and Giles-Corti 2008; Codinhoto 2009). Crime prevention through environmental design (CPTED) has been the most common practice towards an intervention of criminal activity in the built environment; however, little practice has addressed both CPTED and physical activity. While first and second generation crime prevention through environmental design (CPTED) are inclusive of addressing both physical and social aspects of the built environment (Cleveland and Seville 2008; Griffin et al. 2008; Dekeseredy et al. 2009), they have yet to effectively address crime-safety needs and its potential relationship with physical activity behaviors of low-income African-American women and their neighborhoods. Therefore, what built environment changes tailored for this target population—African- American women—are necessary? This study examines 1) what crime safety perceptions of the built environment are affecting low--income African American women’s physical activity levels in Kansas City, Missouri and 2) what design solutions these women suggest could help increase their physical activity levels, through improving their perceptions of neighborhood safety. As a place-specific study on a low income neighborhood in Kansas City, Missouri, selected through GIS suitability analyses with literature-based criteria, this study used survey and focus group interview methods to identify the target group’s design suggestions. The findings resulted with a connection from research to design solutions—neighborhood and street-level design strategies with CPTED guidelines linking the researched participant’s perceptions of crime in their built environment to the effect of crime on their own physical activity.
Keywords: Physical activity; Walkability; Crime Prevention Through Environmental Design (CPTED); Security perceptions; Neighborhood designLow-income African-American women; African American Studies (0296); Landscape Architecture (0390); Public Health (0573)